Person-centred care for migrants: a narrative review of healthcare literature - Son, Cathy; Forsgren, Emma; Öhlén, Joakim; Sawatzky, Richard (Frontiers in Health Services, 2025)
According to the World Migration Report, the number of international migrants has steadily increased in the past 50 years. This has led to an increasing need for healthcare to incorporate a variety of perspectives for migrants. However, healthcare systems still show gaps in accommodating diverse cultural perspectives. Given the increasing attention to person-centred care, there is both an opportunity and a need to explicate how person-centred care (PCC) can help to improve healthcare for migrants. Therefore, we conducted a narrative literature review on cultural dimensions of PCC practice for migrants. A scoping review by Forsgren et al. (2025) identified 1,351 articles from a search of PubMed, Scopus, PsycINFO, CINAHL, and Web of Science databases. From these, nine studies that met the following inclusion criteria were selected: (1) about cultural dimensions of health care for migrants (immigrants and refugees), (2) in any health care settings, (3) written in English, and (4) published within the last 10 years (January 1, 2023-December 31, 2023). The studies included participants from diverse ethnicities, racial backgrounds, and countries of origin. Seven studies were undertaken in primary care, long-term care, or outpatient clinics; one study was on health education; and one additional study focused on the acute care environment. The review led to three main practices: (a) enhancing migrants’ ability to participate in their healthcare, (b) building intercultural partnerships, and (c) promoting cultural education of healthcare providers. These practices underscore the significance of respecting diverse cultural beliefs about shared decision-making and understanding how PCC practice is perceived in different cultural contexts. The results also indicate a need for educational programs that equip healthcare providers with intercultural communication skills and knowledge to provide culturally sensitive PCC. Overall, this study highlights the importance of integrating PCC with interculturalism as a way to foster a more nuanced and responsive understanding of the cultural dimension of care.